144 Ovarian carcinoma long-term survivors: a large single center study at the tübingen university women's hospital. (13th November 2020) - Mittelstadt, S; Grube, M; Engler, T; Walter, CB; Oberlechner, E; Pasternak, J; Hurst, U; Krämer, B; Grischke, E; Brucker, SY; Fischer, AK; Staebler, A; et al.
Abstract : Introduction/Objectives: Most ovarian carcinoma patients present with advanced-stage disease and outcome is fatal in many cases. However, the biological behavior of ovarian carcinoma can be quite variable and long-term survival is reported in up to 30% of patients. It is the aim of this project to identify characteristics associated with long-term survival. Methods: Patients diagnosed with ovarian carcinoma between 2000 and 2012 were identified and follow-up data was collected. In patients who survived for at least 8 years a detailed chart review was performed. Results: A total of n=749 patients with adequate follow-up was identified, of which n=225 (29%) were alive for at least 8 years after diagnosis. Median follow-up was 11.7 years. Median age at diagnosis was 53.5 years. 57% were diagnosed in advanced stage (≥FIGO IIB). Histotyp was found to be high-grade serous in 53%, low-grade serous in 7.9%, mucinous in 7.4%, clear cell in 3.7% and endometrioid in 20% of patients. Median progression free survival was 5.0 years in early, and 2.8 years in advanced-stage patients. Conclusion: Despite ovarian carcinoma being perceived as a highly fatal disease, long-term survival is observed in a substantial number of patients and is not limited to early-stage or low-risk disease. Although prognostic factors are well established, further research of patient characteristics, genetic features and treatment modalities will help to better understand factors contributing to long-term survival. We encourage the scientific community to be aware of this special patient group, which may be key to improving our daily approach to ovarian carcinoma patients.